Computer aided optimal design of RCC silos for bulk storage of grains - BINUJA THOMAS JITHESH R VINODKUMAR B; Dr. V Ganesan (Guide) (Tavanur 1998 department of post harvest technology and agricultural processing)
to study the variation in lateral and vertical pressures encountered due to the stored material . to find out the variation in volume of concrete, steel and area of form work for each element of the silo, with h/d ration....
Computer aided optimal design of RCC silos for bulk storage of grains